Pengaruh Kemandirian Belajar Terhadap Pencapaian Akademik Mahasiswa - Suluh, Melkianus; Bitu, Yuliana Sesi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the influence of learning independence on students' academic achievement in the Basic Physics I course. A quantitative approach was employed using an ex post facto design, in which the independent variable was not directly manipulated by the researcher. The subjects of this study were 20 third-semester students from the Physics Education Study Program at the Catholic University of Weetebula. Data on learning independence were collected through a four-point Likert scale questionnaire, covering aspects such as time management, decision-making in learning, and self-evaluation of learning progress. Meanwhile, academic achievement was measured using a test that assessed students' understanding of vector analysis material. The data were analyzed using descriptive and inferential statistical techniques. The results showed a positive and significant influence between learning independence and students' academic achievement. These findings indicate that the higher the students’ level of learning independence, the better their academic performance. Therefore, fostering learning independence should be a key focus in higher education, particularly in physics instruction.